Evaluation Of The Stiffness And Strength Parameters Of Hardening Soil Model For The Simulation Of The Twin Tunnels Interaction In Kenny Hill Formation Residual Soil - Lim, Siaq Phin (2017)
Numerical simulation for geotechnical problem often involved simplifications and assumptions as it is nearly impossible to simulate all features involved in the ground environment. For large scale construction like Klang Valley Mass Rapid Transit (KVMRT) twin tunnels construction under urban environment, realistic geotechnical simulation is essential. In this study, a parameters determination approach is developed to determine stiffness and strength parameters for Hardening Soil (HS) models based on evaluation of in-situ and laboratory soil testing data for the simulation of twin tunnels interaction in Kenny Hill Formation residual soil. Subsurface characterization conducted to develop three-dimensional (3D) ground models, tunnel filtered models and ground sections for four zones divided from study area based on similarity in lithology and Standard Penentration Test Blow Count (SPT-N) Value distribution. Three critical ground sections were selected based on input of tunnel filtered models and ground sections, twin tunnels configuration associated in respective sections and availability of tunnelling induced ground movement data. The soil profiles and corresponding soil parameters were determined for selected ground sections to develop conceptual model for finite element method (FEM) simulation of tunnelling induced deformation. The soil parameters for Kenny Hill residual soil were evaluated by comparing numerical simulated and in-situ monitored Pressuremeter test (PMT) stress strain curves. The HS model is calibrated by optimization of stiffness and strength parameters to match the in-situ stress-strain curves. Sensitivity analysis of HS parameters influences towards soil behaviour showed that oedometer stiffness has more impact in controlling plastic deformation while unload-reload stiffness has significant effect on the elastic region of soil behaviour. The effectiveness of soil model calibration is determined by back analyses of twin tunnels excavation and verification. The twin tunnels excavation simulation using calibrated HS parameters estimated surface settlement that showed good agreement with construction-monitored ground movements. Meanwhile, Mohr Coulomb (MC) parameters predicted ground movement with surface heave, against the direction of monitoring data. Parametric analysis conducted to determine the influence of tunnels configuration and construction sequence towards twin tunnels interaction in Kenny hill formation residual soil. This study showed an integrated approach for constitutive soil model parameters determination with incorporation of subsurface modelling, constitutive model calibration and verification. The calibrated HS parameters for Kenny Hill formation residual soil contributed as a reference for future construction with similar geological characteristic. The proposed parameters determination method provides a reliable and effective methodology in parameter selection in geotechnical simulation instead of direct correlation from empirical data.